2013
DOI: 10.3109/14767058.2013.766711
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between emergent and elective delivery in women with placenta accreta

Abstract: Antenatal bleeding is associated with an increased risk of emergent delivery. Emergent delivery in a tertiary care facility with immediate access to blood bank and ICU capabilities does not appear to be associated with an increased risk of adverse maternal outcomes. Consequently, some patients may be candidates for delivery later than 34 weeks of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
3
16
1
Order By: Relevance
“…Interestingly, the 2010 decision analysis showed that when a low rate of emergency hemorrhage was assumed (2–8%), the preferred timing strategy would be a 37‐week delivery . Other tertiary centers have shown similarly low rates of morbidity with scheduled and unscheduled accreta deliveries, likely reflecting the ability of an individual institution to assemble a surgical team on short notice . We acknowledge that the low morbidity rates in these retrospective studies likely reflect patient selection, and we offer initial guidance for triaging suspected accreta patients at a tertiary medical center.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the 2010 decision analysis showed that when a low rate of emergency hemorrhage was assumed (2–8%), the preferred timing strategy would be a 37‐week delivery . Other tertiary centers have shown similarly low rates of morbidity with scheduled and unscheduled accreta deliveries, likely reflecting the ability of an individual institution to assemble a surgical team on short notice . We acknowledge that the low morbidity rates in these retrospective studies likely reflect patient selection, and we offer initial guidance for triaging suspected accreta patients at a tertiary medical center.…”
Section: Discussionmentioning
confidence: 91%
“…The ACOG and NICHD recommendations for previa‐accreta delivery at 34 or 35 weeks’ gestation arose from the assumption that maternal morbidity, including but not limited to massive hemorrhage and ICU admission, increases with GA . Here we describe a cohort of patients with previa and suspected accreta in which more than half were delivered at 36 weeks or later.…”
Section: Discussionmentioning
confidence: 99%
“…The mean blood loss in a pregnancy complicated with PA is usually 2.5-3 liters. [16,17] The massive hemorrhage (≥5000 ml estimated blood loss) and massive transfusion (≥10 units erythrocyte transfusion) were observed more in PPA cases. [18] The presence of PP alone even in the patients not within placenta accreta spectrum is an independent factor increasing erythrocyte transfusion and hysterectomy risks.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the 2010 decision analysis showed that when a low rate of emergency hemorrhage was assumed (2-8%), the preferred timing strategy would be a 37-week delivery (4). Other tertiary centers have shown similarly low rates of morbidity with scheduled and unscheduled accreta deliveries, likely reflecting the ability of an individual institution to assemble a surgical team on short notice (17,19). We acknowledge that the low morbidity rates in these retrospective studies likely reflect patient selection, and we offer initial guidance for triaging suspected accreta patients at a tertiary medical center.…”
Section: Discussionmentioning
confidence: 99%